The Impact of Obesity on Hypertension in Adults Aged 25-45 in Padang Lawas Regency in 2024 - Siregar, Nur Khaidah; Ashar, Taufik; Lubis, Rahayu (PT FORMOSA CENDEKIA GLOBAL, 2024)
One of the factors that influence the incidence of hypertension is obesity. The purpose of this study was to analyze the effect of obesity on the incidence of hypertension at the age of 25-45 years in Padang Lawas Regency in 2024. The research method used a case control design with a large sample size of hypertension and non-hypertension of 73 people each. Data analysis using logistic regression test. The results showed that obesity is a factor influencing the incidence of hypertension (OR = 6,056). It is necessary to conduct a public education campaign targeting young adults in Padang Lawas Regency, focusing on the importance of controlling the frequency of fat consumption, healthy types of fat, and associated obesity risks, as well as utilizing social media and holding special counseling sessions for food businesses.